Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/clc.22245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Rehabilitation in Diabetic Patients: Both Cardiac and Noncardiac Factors Determine Improvement in Exercise Capacity

Abstract: Background Diabetic patients have a worse prognosis than nondiabetic patients after myocardial infarction. Although exercise improves risk factors, exercise capacity, and mortality, it is still unclear if these benefits are the same as in nondiabetics. Furthermore, although exercise tolerance is predicted by systolic and diastolic dysfunction in nondiabetics, its role as a predictor of exercise capacity in diabetics remains unclear. Hypothesis Diabetics and nondiabetics see a similar improvement in their cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
8
15
0
Order By: Relevance
“…Similar to prior studies, diabetes proved again to be a negative factor when it comes to functional benefit from CR. [24][25][26] This may stem from the fact that patients with diabetes are less likely to be enrolled in CR, 21,27 and less likely to be adherent. 20,28 Another possible explanation is lower baseline fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior studies, diabetes proved again to be a negative factor when it comes to functional benefit from CR. [24][25][26] This may stem from the fact that patients with diabetes are less likely to be enrolled in CR, 21,27 and less likely to be adherent. 20,28 Another possible explanation is lower baseline fitness.…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes were not as well maintained in patients with diabetes at the 1 year follow-up. Other studies have reported mixed results, with some reporting similar benefits to patients with and without diabetes [25,27,35,36] and others reporting that patients with diabetes had a less marked overall improvement in exercise capacity [37,38]. Although aerobic training is probably the most important component of CR, it should be noted that the TotalCardiology programme also involved addressing conventional risk factors such as lipid control, stress management, nutrition and cessation of cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality has not been widely evaluated. [14][15][16] In a recent and large cohort of 13 000 patients with CAD (2956 with DM), reported by Armstrong et al, 17 CR was associated with significant reductions in mortality and cardiac hospitalizations in patients with DM, similar to outcomes in patients without DM. Although these studies are consistent with our findings, they differ from our study in that they have not been specifically focused on patients who have undergone PCI.…”
Section: Discussionmentioning
confidence: 93%
“…However, several studies have reported that completion of CR in patients with DM is associated with significant benefits on activities of daily living, quality of life, weight control, exercise tolerance, cardiac risk factor control, and risk of mortality. However, mortality has not been widely evaluated . In a recent and large cohort of 13 000 patients with CAD (2956 with DM), reported by Armstrong et al, CR was associated with significant reductions in mortality and cardiac hospitalizations in patients with DM, similar to outcomes in patients without DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation